High frequency of sexually transmitted infections in patients with precancerous cervical lesions in Brazil - Follador, Kerellyn; Viçosa Pires, Leticia; Corbellini, Ana Paula Zanella; Zwir Poli, Jefferson Henrique; Jara Reis, Rosilene; Suñé, Mariana da Silveira; Wink, Priscila Lamb; Cabrera, Giovana; Rosin, Giovana Fontes; Uratani, Fernanda; Kreitchmann, Régis; Mansur, Helena Martins; et al. (Frontiers in Public Health, 2025)
IntroductionCervical cancer is strongly associated with persistent human papillomavirus (HPV) infection, the most common sexually transmitted infection (STI) worldwide. While most infections are cleared naturally, co-infections with non-HPV STIs may contribute to HPV persistence and disease progression. Unlike cervical cancer, which has a national screening program in Brazil, STI screening remains unstructured, with prevalence varying across regions.ObjectiveTo evaluate the prevalence of HPV co-infections with Chlamydia trachomatis, Mycoplasma hominis, Mycoplasma genitalium, Neisseria gonorrhoeae, Ureaplasma urealyticum, and Trichomonas vaginalis in patients diagnosed with cervical intraepithelial neoplasia (CIN) in Porto Alegre, Brazil. Methods: This cross-sectional study included patients with histologically confirmed precancerous cervical lesions attending a referral outpatient clinic. Between October 2022 and December 2023, 159 patients were enrolled and screened for the presence of non-HPV STI co-infections through cervical secretion DNA-qPCR testing.ResultsMost (64.8%) participants were diagnosed with CIN II or III. Among all patients analyzed, nearly 60% had at least one non-HPV STI co-infection associated with low- or high-grade cervical lesions. The most prevalent pathogen was U. urealyticum (44%), followed by M. hominis (16.3%) and C. trachomatis (10.1%).ConclusionA high prevalence of non-HPV STI co-infections was observed in asymptomatic women with CIN, particularly U. urealyticum, which has been identified as a potential cofactor in HPV-related carcinogenesis. Our findings contribute to the growing body of national and international literature supporting the need for integrating STI screening into cervical cancer prevention strategies for sexually active women in Brazil.